Complementizer Agreement and the Position of the Subject in Jordanian Arabic - Alsarayreh, Atef (Dirasat: Human and Social Sciences, 2023)
Objectives: The study aims to investigate the distribution of complementizer agreement in relation to the position of the subject in Jordanian Arabic. Methods: To achieve the objectives of the study, several sentences that manifest complementizer agreement were constructed and presented to 20 native speakers of Jordanian Arabic in written and spoken form. We then asked the informants to read each sentence aloud and judge whether it is acceptable or unacceptable. Results: The interaction of complementizer agreement with the position of the subject in Jordanian Arabic shows that complementizer agreement is sensitive to the active Case requirement for goals (Chomsky 2000, 2001). The distribution of complementizer agreement with coordinated subjects in JA shows that complementizer agreement with a lexical DP is subject to a syntactic locality condition, whereas complementizer agreement with a subject that includes a pronominal element is subject to an adjacency condition, suggesting that a unified analysis of complementizer agreement cannot be maintained. Conclusion: The paper concludes that complementizer agreement in Jordanian Arabic is the result of the operation Agree (Chomsky 2000, 2001), whereby the complementizer functions as a probe with uninterpretable Φ-features that Agrees with a goal with matching interpretable Φ-features.